2011
DOI: 10.1007/s00170-011-3723-6
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory planning of redundant manipulator using fuzzy clustering method

Abstract: The solution of inverse kinematics and trajectory planning with performance criteria for a redundant manipulator is proposed with modification in fuzzy c-means. A new fuzzy clustering model based on a new generalized validity index based on weighted within-scatter metrics and betweencluster scatter metrics for the manipulator is proposed. In order to understand the proposed algorithm and to show its performance, two simulation studies of trajectory planning with manipulability criteria for a redundant manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Robot manipulators are governed by two basic kinematic theories, namely forward kinematics (FK) and inverse kinematics (IK). FK theory calculates the position and orientation of the hand or wrist (end effector) base on the robot's configuration, and the robot's configuration is assumed to be known in terms of all the joint variable angles and the length of links [10,16,17,21,23,34]. Conversely, given the desired position and the orientation of the end effector ( ) t r E , IK theory enables the robot to calculate all the joints values θ, to place itself at the desired location and orientation [10,16,17,21,23,[26][27]29,35].…”
Section: Kinematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Robot manipulators are governed by two basic kinematic theories, namely forward kinematics (FK) and inverse kinematics (IK). FK theory calculates the position and orientation of the hand or wrist (end effector) base on the robot's configuration, and the robot's configuration is assumed to be known in terms of all the joint variable angles and the length of links [10,16,17,21,23,34]. Conversely, given the desired position and the orientation of the end effector ( ) t r E , IK theory enables the robot to calculate all the joints values θ, to place itself at the desired location and orientation [10,16,17,21,23,[26][27]29,35].…”
Section: Kinematicsmentioning
confidence: 99%
“…Basically, there are two types of motion planning for a robot, namely path planning [14][15][16][17] and trajectory planning [7][8][9][12][13][14][18][19][20][21][22]. However, trajectory planning will be more practical compared to path planning as it includes the motion timing, velocities and accelerations.…”
Section: Motion Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling kinematics and dynamic constraints without a loss of transparency and accuracy in master-slave surgical robots remains a challenging task and it has attracted research interests in recent years [6,11,12]. In general, kinematics resolutions basically involve defining apt relationships between the joint and Cartesian spaces of a robot.…”
Section: Introductionmentioning
confidence: 99%
“…are the subject of present research and researchers have suggested various control techniques to tackle some of these problems. Model prediction adaptive controller [3], robust lsynthesis controllers [4,5], intelligent controllers [6][7][8], nonlinear and composite adaptive controller [7,9] and disturbance observer [10] have been used to control such dynamical systems. Further, the environment, operator and task (EOT) adaptive controllers have been considered in [11] highlighting the importance of on-line information for the control.…”
Section: Introductionmentioning
confidence: 99%